Can't Touch That: Safety, Preservation, and Collection Management Assessments of an Education Collection. Issue 2 (June 2023) - Falquero, Kelsey; Hawks, Catharine; Hull-Walski, Deborah; Makos, Kathryn; Palmer, Lisa
Q?rius is an interactive learning venue at the Smithsonian National Museum of Natural History (NMNH) designed specifically for teen audience. The space gives visitors a chance to interact with the museum collection items. These are acquired education collections, belonging to the Office of Education and Outreach (E&O). The collections in Q?rius include 6, 000 specimens representing the Museum's seven disciplines—anthropology, botany, entomology, invertebrate zoology, mineral sciences, paleobiology, and vertebrate zoology. A collaborative survey team was set up to assess collection items before their rehousing and storage in the publicly accessible Collections Zone. The result was a risk rating system, developed to minimize the risks to our visitors and to our collections. This system allows collections staff to make housing recommendations that ensures the safety of NMNH's visitors and the preservation of E&O's publicly accessible collection. The team implemented rankings by using color-coded labels, similar to the universal traffic stoplight system, to indicate whether the public can handle specimens directly (green), handle with assistance from a trained volunteer (yellow), or view only through barriers (red).